(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the efficacy of follicular unit transplantation for androgenic and post burn restoration of hair of beard, scalp hair, side locks and frontal hairline at tertiary care Hospital. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Islamabad Cosmetic Surgery and Department of Plastic Surgery PIMS Islamabad from February 2017 to January 2019. Materials and Methods: Patients presented with scalp burn and androgenic alopecia, age >12 years and either of gender were included. Follicular unit extraction was used for hair restoration, where natural follicles contain 1, 2 or 3 hair and each extracted individually with a 0.9 mm motorized punch and then implanted as hair follicular micro grafts. Follicular unit transplant (FUT) was based on excision of a strip of the scalp to yield hair follicles. Patients underwent the procedure during 2-3 sittings that is spaced 8-10 months apart. Efficacy was recorded in terms of patient’s satisfaction. Data was entered in self-made proforma. Results: Total 78 patients were studied their mean age was 28.23+6.11 years. Males were in majority 61.5%. Out of all 38.5% of grafts grew during 5-6 months, 41.0% of grafts grew in 7-8 months and remaining grew in around 10 months. Survival rate was 84.6% and non-survival rate was 15.4%. Most of the patients were satisfied. Conclusion: Follicular unit transplantation for post burn and androgenic restoration of hair showed best efficacy with excellent survival rate and patients satisfaction. Follicular unit micro skin grafting imparts natural looking layout and replacement for hair restoration of eyebrows, eyelashes, beard, moustache, side burns, hairlines or scalp hair and less noticeable surgical scars.